2022
DOI: 10.1111/pce.14493
|View full text |Cite
|
Sign up to set email alerts
|

A glutathione‐independent DJ‐1/PfpI domain‐containing tomato glyoxalaseIII2, SlGLYIII2, confers enhanced tolerance under salt and osmotic stresses

Abstract: In plants, glyoxalase enzymes are activated under stress conditions to mitigate the toxic effects of hyperaccumulated methylglyoxal (MG), a highly reactive carbonyl compound. Until recently, a glutathione-dependent bi-enzymatic pathway involving glyoxalase I (GLYI) and glyoxalase II (GLYII) was considered the primary MG-detoxification system. Recently, a new glutathione-independent glyoxalase III (GLYIII) mediated direct route was also reported in plants.However, the physiological significance of this new path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…A similar phenomenon was observed in Medicago , in which all of the MtDJ-1 members were expressed under salinity stress along with other stress conditions [ 60 ]. A recent investigation into tomato glyoxalase III (GLYIII) genes revealed that their overexpression enhances salt and osmotic stress tolerance, contributing positively to plant growth and yield [ 68 ]. Further, transgenic tobacco expressing E .…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon was observed in Medicago , in which all of the MtDJ-1 members were expressed under salinity stress along with other stress conditions [ 60 ]. A recent investigation into tomato glyoxalase III (GLYIII) genes revealed that their overexpression enhances salt and osmotic stress tolerance, contributing positively to plant growth and yield [ 68 ]. Further, transgenic tobacco expressing E .…”
Section: Discussionmentioning
confidence: 99%
“…MG induces cellular damage by spontaneously glycating nucleic acids, proteins and lipids. In plants, there are three classes of GLY enzymes – GLYI, GLYII, and GLYIII – among which GLYI and GLYII are glutathione (GSH) and metal cofactor dependent, while GLYIII are GSH‐ and metal ion‐independent enzymes detoxifying MG (Schmitz et al ., 2017; Gambhir et al ., 2023). While GLYI enzymes use Zn as a cofactor in all other eukaryotes, plants have both Zn‐type and Ni‐type GLYI enzymes (Balparda et al ., 2023).…”
Section: Nickelmentioning
confidence: 99%
“…GLX3, a novel glyoxalase enzyme of the DJ-I protein family, directly catalyzes the conversion of MG to D-lactate ( Ghosh et al., 2016 ). Only a few studies have investigated GLX3 in model plants and cereal crops, demonstrating its participation in stress responses ( Jana et al., 2021 ; Kumar et al., 2021 ; Gambhir et al., 2023 ). Recent studies have shown that GLX1 and GLX2 are also involved in regulating seed vigor in Oryza sativa and Arabidopsis ( Schmitz et al., 2017 ; Liu et al., 2022 ), but their role in seed development, storage, and germination is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%